TRADISI DAN RITUAL KEMATIAN WONG ISLAM JAWA - Suwito Suwito; Arif Hidayat; Sriyanto Agus (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
This paper reveals the tradition of Javanese people on handlingthe death. Javanese muslims is understood in a framework of great and little tradition and the meaning in death tradition. Those items when it is revealed and understood practically seems to have a shift. The variation in death tradition because of the distance and the evolution. There are some important highlights; first, Javanese Muslims in understanding and doing the death ritual based on a strong basic as an honour for those who alive and as a symbolic dimension with other nature. Second, Javanese Muslims know that death is a way to go back to Allah so that the everybody should be in a purified condition and still has a belief that Allah is the only one to be worshiped. The people believe that Allah is the Most Forgiving so that Muslims should pray for all the mistakes and bad deed.